Application of multivariate statistical on quality of amazon honey from Apis sp. vs Melipona sp - Gomes, Paulo Wender Portal; Muribeca, Abraão de Jesus Barbosa; Moreira-Neto, João; Gomes, Paulo Weslem Portal; Pereira, Emilli Roberta Sousa; Martins, Luiza Helena da Silva (Scientia Plena, 2020)
This paper aimed to study the quality of honey from genus Apis sp. and Melipona sp from Archipelago of Marajo. The honey was collected from two cities (Soure and Salvaterra). All samples were analyzed for their physicochemical composition, phenolic compounds, antioxidant activity, and analyses of standard quality control of honey. All data were subjected to statistical analysis of Tukey (95%), Person correlation and Multivariate (Principal Component Analysis (PCA) and Grouping Analysis (HCA)). The study resulted in a significant antioxidant potential from Apis sp. (EC50 = 21.14 ± 142.90 µg.mL-1) and Melipona sp. (EC50 = 13.62 ± 198.11 µg.mL-1) by the DPPH (2,2- diphenyl-1-picrylhydrazyl) radical sequestration method. All studied honey presented excellent quality and the presence of secondary metabolites belonging to the class of total phenolic (ranged 27.01 ± 1.01 to 56.09 ± 1.32 mg GAE.100 g-1). In relation to physicochemical and microbiological parameters, all the samples were adequate for use and consumption. The multivariate analysis proved to be a very useful tool for the analysis of different samples of honey. The honey quality is very important since Marajo is a region with great potential for honey production that needs standardization of those products, which deserve greater attention and appreciation.